What'S My Name : Black Vernacular Intellectuals - Farred, Grant (Book collections on Project MUSE., 2003)
In this study of four citizens of the African diaspora--American boxer Muhammad Ali, West Indian Marxist critic C.L.R. James, British cultural theorist Stuart Hall, and Jamaican musician Bob Marley--Farred develops a new category of engaged thinker: the vernacular intellectual. He offers a vision of intellectual activity that is as valid in the boxing ring as in academia.